Feasibility Study For Business Development On Cheap Accessories Rides Surabaya - Mohammad Afrizal Miradji; Bayu Adi; Riyanto, Agung; Mohammad Hisya; Angga Rizal Prayuda; Rizky Mohammad Faiz (Jurnal Ekonomi, 2024)
The reason of this investigate is to decide the possibility of commerce improvement carried out by Cheap Extras Vehicles. The inquire about strategy utilized is an examination based on the viewpoints of commerce achievability considers, specifically viewpoints of Back, Showcase and Promoting, Administration and Human Assets, Lawful, Specialized and Operational angles, AMDAL, and Financial and Social angles. The comes about of the examination of each angle appear positive comes about which state that the Trade Improvement carried out by Cheap Accessories Rides is feasible to run. The conclusion of this study is that the business development carried out by Wahana Accessories Cheap is feasible to be carried out, one of the ways of business development that can be chosen is to extend the number and assortment of items dispersed by the company.